Development of Problem-Based Learning with A Variety of Media to Improve Problem-Solving Skills in Mechanical Wave Material - Odja, Abdul Haris; Dikum, Jepri; Payu, Citron Supu; Supartin, Supartin; Fadly, Wirawan (Jurnal Pendidikan Fisika Indonesia, 2024)
This research aims to produce learning tools that use a problem-based learning model with various media to improve valid, practical, and effective problem-solving skills. This research is a type of research and development (R&D). This research uses the ADDIE model, which stands for Analysis, Design, Development, Implementation, and Evaluation. The research results show that the learning tools are valid, practical, and effective and can be applied in the learning process. The learning tools' validation results are very valid and suitable for use. Practical learning tools with learning implementation results that reach very good criteria and the response given by teachers and students to positive learning tools. Effective learning tools are used to observe student activities, obtain good criteria, and test the results of problem-solving skills for data normality and normal distribution. The completeness of students' problem-solving ability scores is seen from the t-test results, which concludes the students' scores. Learning tools are very influential, as indicated by the value of the effect size test with high criteria. The results of problem-solving skills were increased by increasing the N-gain test in the medium category. Based on the research results, it can be concluded that the learning tools are valid, practical, and effective.